Co-Expression of FOXP3FL and FOXP3Δ2 Isoforms Is Required for Optimal Treg-Like Cell Phenotypes and Suppressive Function - Sato, Yohei; Liu, Jessica; Lee, Esmond; Perriman, Rhonda; Roncarolo, Maria Grazia; Bacchetta, Rosa (Frontiers in Immunology, 2021)
FOXP3 is the master transcription factor in both murine and human FOXP3+ regulatory T cells (Tregs), a T-cell subset with a central role in controlling immune responses. Loss of functional Foxp3 protein in scurfy mice leads to acute early onset lethal lymphoproliferation. Similarly, pathogenic FOXP3 mutations in humans lead to immunodysregulation, polyendocrinopathy, enteropathy, and X-linked (IPEX) syndrome, which is characterized by systemic autoimmunity that typically begins in the first year of life. However, although pathogenic FOXP3 mutations lead to overlapping phenotypic consequences in both systems, FOXP3 in human Tregs, but not mouse, is expressed as two predominant isoforms, the full length (FOXP3FL) and the alternatively spliced isoform, delta 2 (FOXP3d2). Here, using CRISPR/Cas9 to generate FOXP3 knock-out CD4+ T cells (FOXP3KOGFP CD4+ T cells), we restore expression of each isoform by lentiviral gene transfer to delineate their functional roles in human Tregs. When compared to FOXP3FL or FOXP3d2 alone, or double transduction of the same isoform, co-expression of FOXP3FL and FOXP3d2 induced the highest overall FOXP3 protein expression in FOXP3KOGFP CD4+ T cells. This condition, in turn, led to optimal acquisition of Treg-like cell phenotypes including downregulation of cytokines, such as IL-17, and increased suppressive function. Our data confirm that co-expression of FOXP3FL and FOXP3d2 leads to optimal Treg-like cell function, and supports the need to maintain expression of both when engineering therapeutics designed to restore FOXP3 function in otherwise deficient cells.